Influence of external environmental factors on the success of public housing projects in developing countries - Musa, Mohammed Mukhtar (Australian Institute of Quantity Surveyors, 2015)
External environmental factors, which include political environment, economic environment and social environment, affect the success of public housing projects in developing countries. The purpose of this paper is to establish the effect of these factors on public housing project success using structural equation modelling (SEM) techniques. The study was conducted in Nigeria by means of interviews, a pilot study and a main survey. Five hundred and fifty (550) questionnaires were administered to construction professionals who work as developers, consultants or contractors and those working in public housing agencies. Two hundred and seventy-six (276) questionnaires were returned completed. The data collected were analysed by means of SEM. The results reveal that (i) the economics factor significantly affects public housing project success, (ii) the social factor significantly affects public housing project success, and (iii) the political factor significantly affects public housing project success. The study developed a comprehensive model that can assist housing policy makers, consultants, developers, contractors and other stakeholders in the planning and development of public housing programmes